Post-thrombotic syndrome and venous disease-specific quality of life in patients with vascular Behcet's disease - MÜTİŞ ALAN, AYDAN; ALDAĞ, BELGİN; ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN; TOPTAŞ, TAYFUR (ELSEVIER SCIENCE BV, 2016)
Objective: Deep venous thrombosis (DVT) is the most common form of vascular involvement in Behcet's disease (BD). Chronic post-thrombotic syndrome (PTS) develops in up to one-half of patients with DVT and is associated with impaired quality of life (QoL). There are no data on the severity of DVT-related PTS and its effect on QoL in patients with vascular BD (VBD). We aimed to evaluate PTS and venous disease-specific QoL in patients with VBD. Methods: This study included 50 patients (41 men, nine women) with VBD and 31 individuals matched for age and gender (22 men, nine women) with DVT associated with non BD causes. The Villalta scale was used to assess PTS. The Venous Disability Score and the Venous Clinical Severity Score were used for the assessment of venous disease. Venous disease-specific QoL was measured through Venous Insufficiency Epidemiological and Economic Study Quality of Life/Symptom (VEINES-QoL/Sym) questionnaire. The Behcet Syndrome Activity Score (BSAS) questionnaire was used to assess disease activity. Results: We observed a significantly lower risk of PTS together with significantly better VEINES-QoL/Sym, and Venous Disability Score in the VBD group compared with the non BD group. When VBD patients with PTS were compared with patients without PTS, VEINES-QoL/Sym, and Venous Clinical Severity Score were significantly worse. BSAS was also significantly higher in patients with PTS. An inverse correlation was found between the VEINES-QoL and the BSAS in multivariate analysis. There were no differences between anticoagulant users and nonusers regarding the presence of PTS and scores of all of the venous assessment tools. Conclusions: We found lower PTS risk and better venous disease-specific QoL, symptom severity, and venous disability scores in VBD patients compared with the non-BD group. Venous disease-specific QoL negatively correlated with disease activity. Effective control of vascular inflammation through treatment in VBD might explain lower rates of PTS and better venous QoL outcomes in VBD patients. Our results suggest that successful control of BD activity might decrease the development of PTS, improve venous disease-specific QoL, and prevent relapses in VBD.
Keywords: DEEP-VEIN THROMBOSIS; QOL/SYM QUESTIONNAIRE; CONSENSUS STATEMENT; DISORDERS; INFLAMMATION; METAANALYSIS; RELIABILITY; INVOLVEMENT; REVISION; VALIDITY